2022
DOI: 10.1177/1071181322661063
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Virtual Reality-Based Training System for Pilots

Abstract: The successful operation of military aviation depends on effective pilot training. Current training capabilities of the United States Air Force might not be sufficient to meet the demand for new pilots. To help resolve this issue, this implementation study focused on developing an adaptive virtual reality (VR)-based training system for pilots. This prototype was built leveraging the three fundamental components for an adaptive training system including the trainee’s performance measures, adaptive logic, and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In the military domain, VR technologies facilitate diverse training scenarios in simulated environments with varying weather conditions, terrains and day–night cycles (Varol Arısoy and Küçüksille, 2021; Guy, 2020). Reyes et al used VR to develop an adaptive pilot training system (Iván Aguilar Reyes et al , 2022), maintaining pilots’ cognitive abilities. In addition, VR plays a crucial role in demining, reducing the associated dangers.…”
Section: Virtual Reality Technologymentioning
confidence: 99%
“…In the military domain, VR technologies facilitate diverse training scenarios in simulated environments with varying weather conditions, terrains and day–night cycles (Varol Arısoy and Küçüksille, 2021; Guy, 2020). Reyes et al used VR to develop an adaptive pilot training system (Iván Aguilar Reyes et al , 2022), maintaining pilots’ cognitive abilities. In addition, VR plays a crucial role in demining, reducing the associated dangers.…”
Section: Virtual Reality Technologymentioning
confidence: 99%
“…The challenge-point framework suggests that training efficiency is increased by modulating difficulty to account for the skill level of the performer to provide optimal challenge (Guadagnoli and Lee, 2004). Automated training where task difficulty is adaptively matched to skill is known to increase engagement (Missura, 2015;Xue et al, 2017), improve training outcomes (Hunicke, 2005;Lang et al, 2018;Iván Aguilar Reyes et al, 2022), and enhance overall experience and reported stimulation (Schmidt, 1975). However, the effect of personalized rather than standardized progression on training outcomes and flow experience, which depend on how well a training system provides optimal challenge, has not been investigated (Vaughan et al, 2016;Jeelani et al, 2017;Yovanoff et al, 2017).…”
Section: Introductionmentioning
confidence: 99%